Bale Tani and Alang in the Perspective of Science, Local Wisdom and Community Religiosity â€œGumi Sasakâ€ Lombok (Preliminary Study in the Development of Science Learning Devices Based on Local Wisdom and Islamic Values) - Kurniawan Arizona; Gunawan; Ahmad Harjono; Joni Rokhmat; Agus Ramdani; AA Sukarso (Jurnal Penelitian Pendidikan IPA, 2023)
The existence of "Bale Tani" and "Alang" in the present time is now rarely encountered, as they have been replaced by more modern buildings and storage spaces. This research aims to examine "Bale Tani" and "Alang" from a scientific perspective, as well as to explore their significance in terms of local wisdom and the religious beliefs of the Sasak tribe on Lombok Island. This study employs a qualitative method through an in-depth investigation. Researchers directly engage in fieldwork to conduct observations, interviews, and document the objects of study. The research data's credibility is enhanced through triangulation techniques (multiple sources and methods) and supported by relevant reference sources. From a scientific standpoint, both "Bale Tani" and "Alang" are structures designed for disaster mitigation (such as earthquakes and floods) and to protect stored items from humidity, thus preserving them. Based on local wisdom and religiosity, this research reveals several aspects. Notably, their exceptional architectural design and unique forms, which are distinct to Pulau Lombok and not found elsewhere. Their multifunctional nature is highlighted, serving as spaces for storage, rest, gatherings, seating, cooking, and other activities. The alignment of "Bale Tani" towards the east facilitates the determination of the Qibla direction for prayers. The "Alang," functioning as storage for harvest yields, carries the significance of expressing gratitude among the Sasak tribe to their deity for the bestowed sustenance. Consequently, the Sasak community practices frugality by storing their harvest in the "Alang" as a manifestation of this gratitude.